Systems Analysis to Support Transitions Towards Resilient and Sustainable Farming Systems - Kumar, Shalander (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Farm and food systems face mounting challenges including climate risks, resource degradation, poor nutrition outcomes, and unstable farm incomes despite significant agricultural production growth. The high heterogeneity in smallholder farming systems—across resources, risks, preferences, and capacities—necessitates systems-based analytical approaches for effective intervention design. A systems approach enables understanding of feedback loops, identification of leverage points, and recognition of diverse stakeholder roles to facilitate co-creation of solutions. Critical analytical tools include cropping systems suitability analysis, multi-dimensional sustainability assessment, vulnerability indexing, and whole-farm bio-economic modeling. These frameworks help address key questions about accounting for diversity, integrating climate and market risks, and evaluating synergies and trade-offs in whole farming system contexts. Evidence from marginal environments demonstrates the importance of differentiated pathways based on farm typologies, with interventions ranging from enhancing nutritious food access in subsistence systems to reducing transaction costs in market-oriented systems. Scaling sustainable farming systems requires demand-driven production, landscape-level synergies, digital innovations, payment for ecosystem services, and coherent policy frameworks supporting agricultural transformation.